1998
DOI: 10.1093/genetics/148.1.471
|View full text |Cite
|
Sign up to set email alerts
|

Translation of Some Maize Small Heat Shock Proteins Is Initiated From Internal In-Frame AUGs

Abstract: Etiolated maize radicles (inbred Oh43) subjected to a brief heat shock synthesize a family of small heat shock proteins (≃18 kD) that is composed of at least 12 members. We previously described the cDNA-derived sequence of three maize shsp mRNAs (cMHSP18-1, cMHSP18-3, and cMHSP18-9). In this report, we demonstrate that the mRNA transcribed in vitro from one of these cDNAs (cMHSP 18-9) is responsible for the synthesis of three members of the shsp family, and we suggest that cMHSP18-3 may be responsible for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Frappier et al [47] demonstrated that in vitro transcription of the mRNA from the cDNA clone cMHSP18-9 is responsible for the synthesis of three members of the sHSP family in maize and suggested that cMHSP18-3 and cMHSP18-1 may be responsible for the synthesis of five additional members of this family. They further suggested that in maize a single gene might produce a number of different proteins [47]. Although we obtained several deletion clones some of which even encoded shorter peptides with the same open reading frame as Oshsp18.0-CII, our Oshsp18.0-CII has only one protein product (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Frappier et al [47] demonstrated that in vitro transcription of the mRNA from the cDNA clone cMHSP18-9 is responsible for the synthesis of three members of the sHSP family in maize and suggested that cMHSP18-3 and cMHSP18-1 may be responsible for the synthesis of five additional members of this family. They further suggested that in maize a single gene might produce a number of different proteins [47]. Although we obtained several deletion clones some of which even encoded shorter peptides with the same open reading frame as Oshsp18.0-CII, our Oshsp18.0-CII has only one protein product (Fig.…”
Section: Discussionmentioning
confidence: 99%